Telaah Hukum Islam Terhadap Konflik dan Bentrok Fisik di Indonesia - Achmad Alfian; Qadir Gassing; Kurniati Kurniati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Religion as a societal ideology is believed to enable it to become a paradigm for solutions to various conflicts. Islam is a religion that upholds he al-alamin in human life, builds conflict resolution in relation to customary law (ethics, moral values, morals and culture) and state law, which actually originates from Islamic legal discourse. Religion becomes a balancer for conflicts that arise from various indicators, because Islam is a legal consensus that covers various conditions and situations. Religion as an effort to mediate conflict and social friction for the benefit of society. Therefore, Islam as a principle, as a regulator of the order of human life, is a solution to the conflict theory of thought by several experts who show the existence of Islam in it.